Tantangan Kompetisi dan Risiko Monopoli dalam Transformasi Digital E-Commerce dengan Studi Kasus Aplikasi TikTok di Indonesia - Anggraeni, Lenciana Aprilia (Sains: Jurnal Manajemen dan Bisnis, 2023)
Technological developments in Indonesia in the field of trade are increasingly rapid in online use, where the use of the digital economy makes transactions easier throught an increase in the number and value of e-commerce transactions. The use of trade transactions with e-commerce, especially in Indonesia, can create more opportunities for business competition to occur and even more features are provided for making sales through the Tiktok application. Technological improvements can have a significant impact on the country's economic growth. Therefore, the author examines the challenges of competition and the risk of monopoly in the use of the Tiktok application which has a dual function as social media and e-commerce (online buying and selling transactions). The writing of this journal uses a qualitative descriptive method where most of this research proves data obtained from various sources on the official Kominfo and Ministry of Trade websites which are then linked to risks that are likely to occur in the future. The results of this research explain that the practice of using the Tiktok application as both social media and e-commerce can lead to monopoly and unhealthy business competition in the world of commerce. So there is a need for government policies and regulatory updates that need to be implemented to limit the use of the Tiktok application in various circles of society.